The Involvement of Endothelial Progenitor Cell Dysfunction in the Angiographically Defined Coronary Atherosclerotic Patients - Tserendavaa, Sumiya; Enkhtaivan, Odkhuu; Sandag, Tsogtsaikhan; Malchinkhuu, Munkhzol (Central Asian Journal of Medical Sciences, 2020)
Objectives: To evaluate the levels of endothelial progenitor cell-colony forming units in the angiographically defined coronary atherosclerotic patients. Methods: The 10 ml blood was drawn from the peripheral vein of 12-man patients that 4-stable angina, 4 acute myocardial infarction (AMI), and 4 healthy people. Peripheral blood mononuclear cells were isolated by Ficoll density-gradient centrifugation and EPC-CFUs was assayed after two plating and a 6-day culture on fibronectin-coated, 72 well plates, as described. eNOS enzyme titers were determined by ELISA according to the protocol in the cell culture. Results: The people were 52 ± 2.12 years. The number of EPC-CFUs increases with the accordance of patients with stable angina, AMI, healthy people with the statistical significance (H = 15.8, p < 0.001): stable angina (2.6 ± 0.47 colony/well), AMI (6.7 ± 0.81 colony/well), healthy people (10.5 ± 1.34 colony/well). Furthermore, the Kruskal–Wallis test of eNOS enzyme levels in patients with stable angina (5.2 ± 0.61 pg/ml), AMI (8.7 ± 1.49 pg/ml), and healthy people (13.7 ± 2.48 pg/ml). The significant difference (H = 5.7, p < 0.010) was observed among the three groups. The number of EPC-CFUs had a direct significant correlation (r = 0.621, p < 0.001) with the eNOS enzyme levels of this culture. Conclusions: The number of EPC-CFUs and eNOS enzyme levels decrease at patients with stable angina, indicate more than endothelial dysfunction.